Analisis Kinerja Keuangan Bank Sebelum Dan Sesudah Diakuisisi Oleh Investor Asing: Studi Empiris Pada Bank Central Asia Dan Bank Niaga - Yen Sun; Laurentia Dermawan (Binus Business Review, 2011)
Banking industry is one of the most influence factors in the economy growth of one country. However, during 1997-1998 Indonesia banking industry went through hard times because of economic crisis. After that years, many banks were liquidated and restructured. The interesting part is through the restructuring process, several bank acquired by foreign investor and became the foreign-domestic bank. In 2010, some of those banks were in the 10 biggest banks in Indonesia based on asset. Hence, the writer interesting to compare the bank’s financial performance before and after being acquired using two banks as samples of empirical study. Data is based on financial statements published by the companies and Central Bank of Indonesia in 1995-1996, and 2003-2004. Two sample of banks have been selected based on several criteria, they are BCA and Bank Niaga. To analyse their financial performance, several analysis tools will be using, specifically CAMELS (CAR, NPL, NIM, BOPO, LDR minus mangement and sensitivity). The result of the study observed that after being acquired, financial performance of BCA and Niaga Bank is getting better in CAR, NIM, BOPO, but NPL and LDR is less favorable for BCA and so NPL is less favorable for Niaga Bank. Moreover, in terms of profitability analysis, both banks shows better performance. While, the result of credit analysis indicates that the credit risk for both banks is in the stable range at CCC.